2020
DOI: 10.1136/injuryprev-2019-043531
|View full text |Cite
|
Sign up to set email alerts
|

Estimating global injuries morbidity and mortality: methods and data used in the Global Burden of Disease 2017 study

Abstract: BackgroundWhile there is a long history of measuring death and disability from injuries, modern research methods must account for the wide spectrum of disability that can occur in an injury, and must provide estimates with sufficient demographic, geographical and temporal detail to be useful for policy makers. The Global Burden of Disease (GBD) 2017 study used methods to provide highly detailed estimates of global injury burden that meet these criteria.MethodsIn this study, we report and discuss the methods us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 16 publications
1
81
0
Order By: Relevance
“…Third, 95% of patients were admitted with injuries caused by falls and road traffic accidents. This is not a surprising finding, as similar patterns have been found in other trauma centres globally 20 . However, the large proportion of patients (83%) admitted with significant injuries following a fall or road traffic accident and high cause-specific case-fatality rates (up to 10–12.5% in 2012 and 2013) are alarming findings that underline the importance of preventative measures and programmes on road safety and falls; known as a systematic work for trauma pre-event phase 5 , 21 .…”
Section: Discussionsupporting
confidence: 89%
“…Third, 95% of patients were admitted with injuries caused by falls and road traffic accidents. This is not a surprising finding, as similar patterns have been found in other trauma centres globally 20 . However, the large proportion of patients (83%) admitted with significant injuries following a fall or road traffic accident and high cause-specific case-fatality rates (up to 10–12.5% in 2012 and 2013) are alarming findings that underline the importance of preventative measures and programmes on road safety and falls; known as a systematic work for trauma pre-event phase 5 , 21 .…”
Section: Discussionsupporting
confidence: 89%
“…Despite the apparent association between age and decline in both physical and cognitive functions [ 5 ], our results showed that advancing age did not predict the incidence of occasional and recurrent falls. In an age-specific population, the incidence of falls was not age-dependent, as opposed to the prevalence of falls [ 1 ]. This suggests that the number of falls does not increase with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…The global prevalence of falls was 5,186 (4,622–5,849) per 100,000 people in year 2017 [ 1 ]. Falls can lead to debilitating consequences, including injury-related hospitalization, disability and death [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…By introducing the ICH Score to our Emergency Department we could be able to predict the mortality and thus provide better treatment plan and care for the patient. It could also help the treating physician in better explaining the prognosis of the patient to the bystander thereby helping them to cope up mentally with the outcome of the patient [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%